Ethnic Enclaves and the Economic Success of Immigrants - Evidence from a Natural Experiment - Per-Anders Edin; Peter Fredriksson; Olof Åslund (Uppsala University, Department of Economics, 2000)
Recent immigrants tend to locate in ethnic enclaves within metropolitan areas. The economic consequence of living in such enclaves is still an unresolved issue. We use an immigrant policy initiative in Sweden, when government authorities distributed refugee immigrants across locales in a way that may be considered exogenous. This policy initiative provides a unique natural experiment, which allows us to estimate the causal effect on labor market outcomes of living in enclaves. We find substantive evidence of sorting across locations. When sorting is taken into account, living in enclaves improves labor market outcomes; for instance, the earnings gain associated with a standard deviation increase in ethnic concentration is in the order of four to five percent.
urn:nbn:se:uu:diva-2505
Keywords: J15; J18; R23; 330; Immigration; Enclaves; Labor market outcomes; Einwanderung; Einkommen; Schweden; Migranten; Segregation